2018
DOI: 10.2478/enr-2018-0009
|View full text |Cite
|
Sign up to set email alerts
|

Co-exposure to endocrine disruptors: effect of bisphenol A and soy extract on glucose homeostasis and related metabolic disorders in male mice

Abstract: Soy extract may protect against some adverse effects of BPA. These findings represent the first report suggesting a potential effect between soy extract and BPA in low doses, however, further studies are needed to confirm these results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 46 publications
0
7
0
Order By: Relevance
“…(28,29) Given their deregulatory properties, EDCs may impact glycoregulatory hormones. (30) Pre and postnatal exposure to glyphosate (Roundup Original DI  ) increased glucose sensitivity in the GBH-F1 Group on PND60 in this study. Although this parameter was normalized by PND143, glucose level decline after insulin administration was significantly higher in the GBH-F1 compared to the CTRL-F1 Group, suggesting higher sensitivity to this hormone.…”
Section: Liver Histology In Male F1 Offspringmentioning
confidence: 48%
See 1 more Smart Citation
“…(28,29) Given their deregulatory properties, EDCs may impact glycoregulatory hormones. (30) Pre and postnatal exposure to glyphosate (Roundup Original DI  ) increased glucose sensitivity in the GBH-F1 Group on PND60 in this study. Although this parameter was normalized by PND143, glucose level decline after insulin administration was significantly higher in the GBH-F1 compared to the CTRL-F1 Group, suggesting higher sensitivity to this hormone.…”
Section: Liver Histology In Male F1 Offspringmentioning
confidence: 48%
“…Tizhe et al (31) reported a subtle (non-significant) increase in plasma glucose and insulin levels in male rats exposed to different concentrations of Bushfire  (a commercial formulation of glyphosate). Veissi et al (30) observed increased glycemia and decreased insulinemia in male mice exposed to Bisphenol A (BPA) (diphenol used in plastic products, with endocrine disrupting effects). According to Bonvallot et al (32) exposure to a mixture of eight pesticides commonly found in the environment may interfere with glycemic metabolism by increasing hepatic glucose production in dams and their offspring.…”
Section: Liver Histology In Male F1 Offspringmentioning
confidence: 99%
“…It is important to note that hyperinsulinemia may eventually lead to insulin resistance and, therefore, may contribute to obesity and T2DM development ( 33 , 100 ). In contrast, other reports described decreased plasma insulin levels after exposing mice to 100 μg/kg/day BPA for 20 days ( 101 ) or 28 days ( 102 ), or even unchanged plasma insulin levels after 8 months of BPA administration (5–5,000 μg/kg/day) ( 103 ). These discrepancies in the observed outcomes might be due to the use of different mouse strains and/or variations in the administration protocol.…”
Section: Metabolic Consequences Of Adult Exposure To Bpamentioning
confidence: 88%
“…In resin-based composites and sealants in dentistry, BPA levels were reported to range from 0.5 to 84.4 μg per 100 mg of commercial product, and the saliva samples obtained after treatment using these products contained 3.3 to 30.0 μg/mL (approximately 14.5 to 131.4 μM) [ 32 ]. In some animal studies, long-term exposure to 0.1–10 mg/kg/day BPA decreased plasma insulin levels and increased the number of active caspase-3- positive cells in the pancreatic islets (approximately 0.44–43.8 μM/day), which accelerated DM development [ 33 , 34 ]. More importantly, MBP, as an active metabolite of BPA, is formed upon coincubation of BPA and liver microsomal and cytosolic fractions (S9 fraction from mammalian liver samples, including human samples) [ 11 ].…”
Section: Discussionmentioning
confidence: 99%